PENERAPAN KOMUNIKASI EDUKATIF BERBASIS QAULAN DALAM INTERAKSI GURU DAN ANAK DI RA ASY' SYAMSU KABUPATEN BULUKUMBA - Nova Rimadani; Sumiati Wahyuni; Novita Sari; Nurwajah; A.Nidha Eka Restuti Munawir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of qaulan-based educational communication in teacher-child interactions at RA Asy’ Syamsu, Bulukumba Regency, and to identify the forms of communication used by teachers to support early childhood development. This study employed a descriptive qualitative approach. Participants included three teachers, while 12 children were observed during teaching and learning activities. Data were collected through observation, interviews, and documentation and analyzed using Miles, Huberman, and Saldaña’s interactive model, including data condensation, data display, and conclusion drawing and verification. The findings indicate that teachers implemented the six qaulan principles in learning activities by conveying honest information, using polite and comprehensible language, respecting children’s opinions, and providing motivation and positive reinforcement. These communication practices positively contributed to children’s language skills, self-confidence, social-emotional development, and character formation. However, implementation was constrained by teachers’ emotional conditions, differences in children’s characteristics, and limited continuity of communication between school and family. Therefore, qaulan-based educational communication can serve as an approach to creating a conducive learning environment and supporting the holistic development of early childhood.